Does cycloheximide-induced loss of phosphate uptake activity in Neurospora crassa reflect rapid turnover? - Beever, R E (1978)
Addition of cycloheximide to Neurospora crassa germlings growing in liquid medium caused an exponential loss of phosphate uptake activity (half-life, ca. 2 h). No loss of activity resulted when germlings were resuspended, at the time of cycloheximide addition, in medium of a substantially lower phosphate concentration. It is concluded that the phosphate uptake systems are not subject to rapid turnover.